Metode Perhitungan Pembagian Warisan dengan Angka Asal Masalah - T Saifullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Fiqh al-mawaris is one branch of Islamic jurisprudence that regulates the procedures for transferring a deceased personals estate to his or her heirs in accordance with Islamic law. The distribution of inheritance in Islam is governed by detailed rules, both regarding the parties who are entitled or not entitled to inherit and the proportion of shares received by each heir. This paper aims to explain the concept of fiqh al-mawaris its conceptual foundations in Islam, and the method of calculating inheritance distribution using the concept of asal al-masalah (the base number). In addition, this study discusses the stages of inheritance settlement, including the fulfillment of the deceased of obligations, the settlement of debts, the separation of jointly owned property, and the conversion of inherited assets into monetary value. Through a systematic understanding of calculation methods and the principles of fiqh al-mawaris, it is expected that inheritance distribution can be carried out fairly, proportionally, and in accordance with the provisions of Islamic law.